Psychosocial Framework of Resilience: Navigating Needs and Adversities During the Pandemic, A Qualitative Exploration in the Indian Frontline Physicians - Banerjee, Debanjan; Sathyanarayana Rao, T. S.; Kallivayalil, Roy Abraham; Javed, Afzal (Frontiers in Psychology, 2021)
Introduction Frontline healthcare workers (HCW) have faced significant plight during the ongoing Coronavirus disease 2019 (COVID-19) pandemic. Studies have shown their vulnerabilities to depression, anxiety disorders, post-traumatic stress, and insomnia. In a developing country like India, with a rising caseload, resource limitations, and stigma, the adversities faced by the physicians are more significant. We attempted to hear their “voices” to understand their adversities and conceptualize their resilience framework. Methods A qualitative approach was used with a constructivist paradigm. After an initial pilot, a socio-demographically heterogeneous population of 172 physicians working in COVID-designated centers were purposively sampled from all over India. Following in-depth virtual interviews using a pre-formed semi-structured guide, the data was transcribed and translated verbatim. The interview was focused on their challenges, needs, and processes of coping and support. Charmaz’s grounded theory was used for analysis supplemented by NVivo 10 software. Results Fear of infection, uncertainty, stigma, guilt, and social isolation emerged as the main challenges. Simultaneously, their “unmet needs” were flexible work policies, administrative measures for better medical protection, the sensitivity of media toward the image of HCW, effective risk communication for their health, and finally, social inclusion. Their resilience “framework” emerged as a process while navigating these adversities and consisted of three facets: forming a “resilient identity,” managing the resilience, and working through the socio-occupational distress. The role of mental well-being, social network, peer support, problem negotiation, and self-care emerged as the key coping strategies. Conclusion The study findings support the global call for better psychosocial health and quality of life of the frontline HCWs. Their “unheard voices” explored in the study can anchor subsequent resilience-enhancing interventions and policies. Guidelines focusing on the psychological wellbeing of frontline HCWs need to be grounded in their unmet needs and lived experiences.